2018
DOI: 10.1159/000490372
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Oxygen Saturation Targeting, and Retinopathy of Prematurity Screening and Treatment Criteria in Neonatal Intensive Care Units: An International Survey

Abstract: Background: Rates of retinopathy of prematurity (ROP) and ROP treatment vary between neonatal intensive care units (NICUs). Neonatal care practices, including oxygen saturation (SpO2) targets and criteria for the screening and treatment of ROP, are potential contributing factors to the variations. Objectives: To survey variations in SpO2 targets in 2015 (and whether there had been recent changes) and criteria for ROP screening and treatment across the networks of the International Network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…11 Previously, we reported a significant variation in outcomes between the participating iNeo countries 16 as well as differences in some practices. [17][18][19][20][21] In this study, our aim was to analyze trends in the health outcomes of neonates born very preterm in 11 highincome countries. The impetus for this comparison came from iNeo objectives to understand variation, foster discussion and collaboration, and identify areas for improvement through the assessment of changes in neonatal outcomes within countries over time.…”
mentioning
confidence: 99%
“…11 Previously, we reported a significant variation in outcomes between the participating iNeo countries 16 as well as differences in some practices. [17][18][19][20][21] In this study, our aim was to analyze trends in the health outcomes of neonates born very preterm in 11 highincome countries. The impetus for this comparison came from iNeo objectives to understand variation, foster discussion and collaboration, and identify areas for improvement through the assessment of changes in neonatal outcomes within countries over time.…”
mentioning
confidence: 99%
“…Multicenter, randomized and large-scale clinical trials have shown SpO 2 below 90%, during intensive care stay, Fig. 1 SpO 2 ranges used in participating NICUs are associated with a higher mortality, and saturation values higher than 95% are associated with increased morbidity [11,12,22]. The present study allowed to draw a representative picture of how the management of oxygen monitoring is performed in 93 neonatal intensive care units in Italy and which factors independently favored/refrained the use of the recommended targets.…”
Section: Discussionmentioning
confidence: 99%
“…To date there is no standardized SpO 2 interval, universally recognized as excellent by the scienti c community, to guarantee tissue oxygenation in the NICU setting. Multicenter, randomized and large-scale clinical trials have shown SpO 2 below 90%, during intensive care stay, are associated with a higher mortality, and saturation values higher than 95% are associated with increased morbidity [8,9,21]. Our study showed in 64.4% of the centers the lower limit of SpO 2 is set below 90%, highlighting a propensity to tolerate hypoxia; in contrast, in 24.4% of the centers the upper limit of SpO 2 is set above 95% re ecting a permissive attitude towards hyperoxia.…”
Section: Discussionmentioning
confidence: 99%